Tendon mechanobiology in the context of tendon biofabrication - Gögele, Clemens; Pattappa, Girish; Tempfer, Herbert; Docheva, Denitsa; Schulze-Tanzil, Gundula (Frontiers in Bioengineering and Biotechnology, 2025)
Tendons are often affected by injuries or tendinopathies, resulting in serious and long-lasting impairments. The repair capacity is very low with a high risk of rerupture. Nevertheless, early, moderate and intermittent functional training adapted to the healing process has been shown to support tendon healing. The mechanosensitive tenocytes are responsible for extracellular matrix (ECM) synthesis, a process that is highly dependent on their specific and local mechanotopographical niche. The mechanical stimuli are triggered by the surrounding ECM that are then recognized by the cells via mechanosensation, transduced via activated intracellular molecular cascades to initiate the mechanoresponse, a process known as mechanotransduction. Hereby, the activation of calcium (Ca2+) dependent channels plays an essential role. Moreover, tenocyte primary cilium has been strongly suggested to participate in mechanosensation and -transduction. The cellular mechanoresponse results in processes such as ECM remodeling, collagen fiber alignment, cell proliferation and migration. Diverse approaches have been developed to recapitulate the natural mechanoenvironment and to optimize tenogenesis. It still remains difficult to identify the threshold parameters that determine optimal mechanical stimulation of tenocytes. The diverse effects of mechanical loading on tenocytes are not yet fully understood, as 2D and 3D experiments have not led to consistent conclusions. Further research is needed to fully address the mechanomics of each tendon cell population to gain a more comprehensive picture of cellular mechanoresponses and interdependencies within the tendon tissue that could help to explain possible feedback mechanisms for the regulation of the tendon ECM after mechanical loading. In turn, such efforts and subsequent achievements can help to outlining advanced therapeutic strategies and physiotherapy protocols for tendon health. Future developments in the field of mechanically assisted tendon reconstruction include 4D applications and direct in situ bioprinting.